2015
DOI: 10.1007/s00383-015-3691-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of preformed silos in the management of infants with gastroschisis: a systematic review and meta-analysis

Abstract: The quality of evidence comparing PFS with alternate treatment strategies for gastroschisis is poor. Only routine use of PFS is associated with fewer days on a ventilator compared with other strategies. No strong evidence to support a preference for any strategy was demonstrated. Prospective studies are required to investigate the optimum management of gastroschisis. Standardised outcome measures for this population should be established to allow comparison of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
1
34
0
6
Order By: Relevance
“…Also, the presence of significant bowel edema and concomitant risk of bowel ischemia/compartment syndrome precluded attempts at primary closure. In addition to these, we do not have the capacity for neonatal mechanical ventilation and studies have shown that the use of preformed silos is associated with lower requirements for ventilation (18)(19)(20), reduced time to feeding, lower infection rates and lower risk of abdominal compartment syndrome (20). However, preformed silos are not available in our setting, so we improvised using the female condom initially and switched to urobag subsequently, because urobag is stronger and does not tear easily like the condom.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the presence of significant bowel edema and concomitant risk of bowel ischemia/compartment syndrome precluded attempts at primary closure. In addition to these, we do not have the capacity for neonatal mechanical ventilation and studies have shown that the use of preformed silos is associated with lower requirements for ventilation (18)(19)(20), reduced time to feeding, lower infection rates and lower risk of abdominal compartment syndrome (20). However, preformed silos are not available in our setting, so we improvised using the female condom initially and switched to urobag subsequently, because urobag is stronger and does not tear easily like the condom.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies reported 'Mortality' [8][9][10][11][12][13], while only two reported outcomes relating to 'Life impact', [9,10]. Only two studies, [9,10] reported outcomes assigned to all five core areas, four studies reported outcomes relating to four core areas, [8,[11][12][13] and two studies, [1,7] reported outcomes relating to only three of the core areas.…”
Section: Resultsmentioning
confidence: 89%
“…A total of eight articles met the inclusion criteria and all were included. These included three RCTs and five systematic reviews, [1,[7][8][9][10][11][12][13]. Data from a total of 4398 infants were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal method of gastroschisis reduction and closure in HICs remains controversial. The two most commonly utilised methods are primary closure under general anesthesia in the operating room or serial reductions using a preformed silo over a number of days followed by either bedside or operating room closure, with or without a general anesthetic 46,47 . Allotey compared 53 consecutive neonates that underwent either primary closure or preformed silo application and reported lower mean airway pressures and inspired oxygen requirement, higher urine output and no inotropic support in the latter group; 43% of those undergoing primary closure required inotropes 48 .…”
Section: Gastroschisis Reduction and Closurementioning
confidence: 99%